Gap Analysis of Employability Skills of Entry Level Business Graduates Based on Job-Fit Theory - Metilda, R Mary; P.C., Neena (International Journal of Social Sciences and Management, 2016)
This paper analyzes the perceptions of the employer on how job fit is fresh business school graduates in the Indian business scenario. The responses of employers on skills considered in the recruitment of management graduates, matching to their business profile as well as job profiles, were compared with the actual skill set of fresh MBAs inducted from the higher education sector. This study also investigated the level of importance of skills required by a new business graduate from the employer’s expectations of different sectors. A ‘skill gap’ between actual and expected was identified from these findings and its impact will be an eye opener for Business education programs. This is a working paper based on classification of employability skills based on Holland’s Job-fit theory. The study reveals that there is substantial dissatisfaction with the quality of business graduates in the practical level. The survey said 86 percent of employers concurred that MBA-hires doesn’t create much value for their companies in their first few years of their career stage. This confirms the finding that the skill set of fresh managers is inadequate. There will be drastic changes in the Job market and the need of the skill sets may vary again and again. The results of this study make a valuable contribution to the field of career development/guidance, individual students of business studies, employers, and higher education institutions. Int. J. Soc. Sc. Manage. Vol. 3, Issue-4: 294-299